Sistem Manajemen Informasi Kesehatan pada Suatu Desa untuk Mewujudkan Desa Sehat - Santoso, Fahrurozi (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
The purpose of this research is to find out the overview of knowledge of information management systems in the village. This research design uses descriptive designs The population in the study was 188 pregnant women, with a sample of 38 respondents using accidental sampling techniques. Data collection uses primary data and secondary data with univariate analysis. The results of the study were obtained from respondents: 16 pregnant women (42.1%) had less knowledge, a small proportion of respondents (15 pregnant mothers (39.5%) had enough knowledge, while very few of the respondents had a good knowledge of 7 people (18.4%). The conclusion of the knowledge of pregnant mothers in the village of Wajok Hilir is very poor due to the poor education of the mother, therefore, the factor that caused the pregnant mother to refuse to test the pregnancy because of the lack of knowledge of the risk of pregnancies.